Recognition of social health: A conceptual framework in the context of dementia research - Vernooij-Dassen, Myrra; Verspoor, Eline; Samtani, Suraj; Sachdev, Perminder S.; Ikram, M. Arfan; Vernooij, Meike W.; Hubers, Claudia; Chattat, Rabih; Lenart-Bugla, Marta; Rymaszewska, Joanna; Szczesniak, Dorota; Brodaty, Henry; et al. (Frontiers in Psychiatry, 2022)
Objective The recognition of dementia as a multifactorial disorder encourages the exploration of new pathways to understand its origins. Social health might play a role in cognitive decline and dementia, but conceptual clarity is lacking and this hinders investigation of associations and mechanisms. The objective is to develop a conceptual framework for social health to advance conceptual clarity in future studies. Process We use the following steps: underpinning for concept advancement, concept advancement by the development of a conceptual model, and exploration of its potential feasibility. An iterative consensus-based process was used within the international multidisciplinary SHARED project. Conceptual framework Underpinning of the concept drew from a synthesis of theoretical, conceptual and epidemiological work, and resulted in a definition of social health as wellbeing that relies on capacities both of the individual and the social environment. Consequently, domains in the conceptual framework are on both the individual (e.g., social participation) and the social environmental levels (e.g., social network). We hypothesize that social health acts as a driver for use of cognitive reserve which can then slow cognitive impairment or maintain cognitive functioning. The feasibility of the conceptual framework is demonstrated in its practical use in identifying and structuring of social health markers within the SHARED project. Discussion The conceptual framework provides guidance for future research and facilitates identification of modifiable risk and protective factors, which may in turn shape new avenues for preventive interventions. We highlight the paradigm of social health in dementia as a priority for dementia research.